2015
DOI: 10.4314/gmj.v48i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing performance of amoxicillin and intramuscular benzathine penicillin in relieving manifestations of <i>Streptococcal pharyngitis</i> in children

Abstract: SUMMARYObjective: To compare clinical and bacteriologic responses to intramuscular benzathine penicillin G (BPG) and single dose of amoxicillin in Group A streptococcal (GAS) pharyngitis. Design: This study included 571 children from 6 to 15 years old age, with pharyngitis, who were admitted to 45 elementary and guidance schools from 7 regions of Education Organization in North-East of Iran, Mashhad. They were screened for enrollment and if he/she presented pharyngitis with clinical criteria of sore throat, er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…We should explain that this article and the similar article[ 13 ] were derived from a research project that had been funded by a grant from the research and education foundation of our university with the code: NCT01310361.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We should explain that this article and the similar article[ 13 ] were derived from a research project that had been funded by a grant from the research and education foundation of our university with the code: NCT01310361.…”
Section: Methodsmentioning
confidence: 99%
“…This research project as a cross-sectional study performed on 6–15-year-old elementary and high-school children from seven different regions of North-East of Iran, Khorasan, Mashhad, from March 2012 to March 2013. [ 13 ] They were screened for enrollment as pharyngitis with clinical criteria of sore throat, erythema, exudate, and tender or enlarged anterior cervical lymph nodes (larger than 1.5 cm). Exclusion criteria were considered: Oral antibiotics use within the preceding 3 days or intramuscularly administered antibiotics within the 28 days prior to the visit which may modify clinical presentation of streptococcal pharyngitis, history of previous ARF or rheumatic heart disease, presence of another illness, and to be carrier.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, IM benzathine penicillin G may be used for patients deemed to have difficulty complying with a 10-day oral antibiotic regimen [ 12 60 61 ]. Studies have found no significant differences in the clinical efficacy of 10-day amoxicillin oral antibiotic therapy and single IM injection of benzathine penicillin G [ 61 62 ].…”
Section: Recommendationsmentioning
confidence: 99%